2017
DOI: 10.1117/12.2265398
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact vibration analysis using speckle-based techniques

Abstract: In this work, two different speckle based techniques are employed to quantify the movement of a vibrating surface. Directly projecting a coherent laser to a rough surface and collecting its associated subjective speckle using a high-speed camera, different frequencies are detected successfully. For the same purpose, a speckle pattern created by launching a coherent laser within a multimode fiber is employed as structured light to detect changes into the projection surface. The achieved results suggest that sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…We have compared six signal recovery algorithms in terms of the quality of the recovered signal and the computational costs. We have considered the differential processing method used in [11,12] which is simple to implement, but introduces undesired nonlinearities. We have analyzed how the mean intensity of the speckle pattern can recover the audio signal and have shown that a single observed pixel, if it is appropriately selected (the pixel with largest variance) can be sufficient for obtaining a reasonably good recovery of the audio signal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have compared six signal recovery algorithms in terms of the quality of the recovered signal and the computational costs. We have considered the differential processing method used in [11,12] which is simple to implement, but introduces undesired nonlinearities. We have analyzed how the mean intensity of the speckle pattern can recover the audio signal and have shown that a single observed pixel, if it is appropriately selected (the pixel with largest variance) can be sufficient for obtaining a reasonably good recovery of the audio signal.…”
Section: Discussionmentioning
confidence: 99%
“…Diode lasers are particularly attractive for sensing applications due to the fact that they are compact, energy-efficient, low-cost, and cover a wide range of wavelengths. Because of these advantages, here we implement the setup proposed by Rodriguez-Cobo et al [11] and Robles-Urquijo et al [12] for the remote recovery of audio signals from videos of speckle patterns [13], but using a diode laser. In our setup the output of the laser is projected to the membrane of a loudspeaker and the movement of the speckle pattern when the speaker plays a sound is video-recorded with a CCD camera.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations